KONTRIBUSI HASIL HUTAN BUKAN KAYU (GETAH DAMAR DAN GULA AREN) TERHADAP PENDAPATAN MASYARAKAT DAN UPAYA KEBERLANJUTANNYA DI DESA LUMOLI KABUPATEN SERAM BAGIAN BARAT - Audry Audeta Rawul; Thomas M. Silaya; Mersiana Sahureka (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This study aims to investigate the contribution of non-timber forest products, specifically damar resin and palm sugar, to community income and the efforts to sustain them in Lumoli Village, West Seram District, West Seram Regency. The research employed a survey method with purposive sampling involving 30 non-timber forest product farmers and was analyzed qualitatively and quantitatively. The results indicate that damar resin and palm sugar contribute significantly to household income, each accounting for over 95% of total income. Traditional management methods combined with local wisdom such as the sasi system support resource sustainability. However, challenges such as limited market access and price fluctuations remain major obstacles. Sustainability efforts are carried out through strengthening social capital and providing product management training. The study recommends improving market access and facilitating processing technology to increase product added value while preserving the environment.